2005
DOI: 10.1177/000331970505600102
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Heparin Spray: A New Formula in Adjunctive Treatment of Superficial Venous Thrombosis

Abstract: The objective of this study was to assess the efficacy and safety of liposomal heparin spray-a new formula of topical heparin delivery. This was a randomized, multicenter, controlled open clinical trial with 2 parallel groups. Forty-six outpatients with clinical signs of superficial venous thrombosis (SVT) were treated with either topical liposomal heparin spraygel (LHSG) (Lipohep Forte Spraygel, 4 puffs of 458 IU tid (n = 22) or with low-molecular-weight heparin (LMWH) (Clexane 40 mg once a day (n = 24), admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 14 publications
0
10
0
3
Order By: Relevance
“…, 2007), cutaneous leishmaniasis (Ferreira et al. , 2004), varicose veins (Gorski et al. , 2005), ocular lesions (Danion et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2007), cutaneous leishmaniasis (Ferreira et al. , 2004), varicose veins (Gorski et al. , 2005), ocular lesions (Danion et al.…”
Section: Discussionmentioning
confidence: 99%
“…This supports other research which has evaluated liposome-based formulations of drugs. In humans, liposomes have been investigated for use in numerous applications including treatment of rheumatoid arthritis (Cher-evatov et al, 1987), neoplastic conditions (Carvalho Junior et al, 2007), cutaneous leishmaniasis (Ferreira et al, 2004), varicose veins (Gorski et al, 2005), ocular lesions (Danion et al, 2007), hair loss (Mura et al, 2007), and for transcutaneous vaccination (Gupta et al, 2005). Therefore, it is plausible that liposome-based diclofenac has the potential to be an important alternative to parenteral NSAID therapy.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The safety and efficacy of a liposomal heparin spray in the treatment of superficial venous thrombosis has been studied in human subjects. 9 We have recently studied the safety and efficacy of pegylated cationic liposomal formulation of LMWH and demonstrated that the duration of action of cationic liposomal formulations of LMWH was longer than that of plain LMWH administered via the pulmonary route. Further, our study showed that liposomal formulations administered at a reduced dosing frequency produced thrombolytic effects similar to that produced by plain subcutaneous LMWH.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, and 2005 two studies of the same design [11,12] concluded that LMWH is equally effective in comparison with topically applied heparin regarding the reduction of erythema, swelling and pain. Another study [13], compared LMWH with topically applied heparin in alleviating the above mentioned symptoms.…”
Section: Discussionmentioning
confidence: 99%